Sowing the field : Greek and Roman sexology - King, Helen (Sexual knowledge, sexual science : the history of attitudes to sexuality, Sexual knowledge, sexual science : the history of attitudes to sexuality)
"Fonds Suzan Daniel (FSD) Helen King"